Sustainability of fiscal policy in Polish voivodeships - Banaszewska, Monika (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The recent financial and economic crisis turned out to be a catalyst for a sovereign debt crisis in some countries. As a result, the issue of fiscal (in)sustainability has been high on the agenda of economic research and economic policy. In the case of a decentralized government system one should take into account the division of public debt between respective levels of the government. The aim of the article is to verify whether Polish voivodeships conduct sustainable fiscal policies. The impact of fiscal equalization scheme (both vertical and horizontal ones) is also considered. In particular, it is worth examining whether fiscal rules imposed on local government entities counterbalance a soft budget constraint problem. The article uses panel data analysis in conjunction with Bohn’s model of fiscal sustainability. The results of the analysis support the hypothesis of sustainability of fiscal policies in Polish voivodeships in the period 2004-2012
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2017, Nr 482, s. 9-16
Keywords: local government; public debt; Bohn’s model; samorząd lokalny; dług publiczny; model Bohna